Analisis Hukum terhadap Perlindungan Pekerja Migran Indonesia Pasca Pencabutan Moratorium Penempatan ke Arab Saudi - Putri Naila (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study examines the legal protection of Indonesian Migrant Workers (PMI) following the revocation of the moratorium on deployment to Saudi Arabia. Using a normative juridical approach with a descriptive-analytical specification, the research explores the effectiveness of Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, the impact of the moratorium revocation on the rights and security of PMI, and the implementation of bilateral cooperation through the Indonesia–Saudi Arabia Memorandum of Understanding (MoU). The findings reveal that although the existing legal framework is comprehensive, its implementation remains weak, particularly regarding supervision and law enforcement in destination countries. The study identifies a gap between administrative regulations and substantive protection, as reflected in the persistent cases of violence, delayed wages, and exploitation in the domestic sector. Strengthening the effectiveness of PMI protection requires synergy between legal reform, digital-based monitoring systems, and human rights–based diplomacy. Therefore, Indonesia must reinforce its political commitment, institutional coordination, and bilateral mechanisms to ensure the fulfillment of migrant workers’ fundamental rights and dignity abroad.